Topological weak-measurement-induced geometric phases revisited - Puentes, Graciana (Frontiers in Physics, 2025)
We present an analytical and numerical study of a class of geometric phase induced by weak measurements. In particular, we analyze the dependence of the geometric phase on the winding (W) of the polar angle (φ), upon a sequence of N weak measurements of increased magnitude (c), resulting in the appearance of a multiplicity of critical measurement-strength parameters where the geometric phase makes a |π| discrete jump. Adding to the novelty of our approach, we not only analyze the weak-measurement-induced geometric phase by a full analytic derivation, valid in the quasi-continuous limit (N→∞), but also we analyze the induced geometric phase numerically, thus enabling us to unravel the finite-N interplay of the geometric phase with the measurement-strength parameter, and its stability to perturbations in the measurements protocol.